Amount, not strength of recollection, drives hippocampal activity: A problem for apparent word familiarity‐related hippocampal activation. Issue 1 (8th November 2018) - Mayes, Andrew R.; Montaldi, Daniela; Roper, Adrian; Migo, Ellen M.; Gholipour, Taha; Kafkas, Alex
Abstract : The role of the hippocampus in recollection and familiarity remains debated. Using functional magnetic resonance imaging (fMRI), we explored whether hippocampal activity is modulated by increasing recollection confidence, increasing amount of recalled information, or both. We also investigated whether any hippocampal differences between recollection and familiarity relate to processing differences or amount of information in memory. Across two fMRI tasks, we separately compared brain responses to levels of confidence for cued word recall and word familiarity, respectively. Contrary to previous beliefs, increasing confidence/accuracy of cued recall of studied words did not increase hippocampal activity, when unconfounded by amount recollected. In contrast, additional recollection (i.e., recollecting more information than the word alone) increased hippocampal activity, although its accuracy matched that of word recall alone. Unlike cued word recall, increasing word familiarity accuracy did increase hippocampal activity linearly, although at an uncorrected level. This finding occurred although cued word recall and familiarity memory seemed matched with respect to information in memory. The detailed characteristics of these effects do not prove that word familiarity is exceptional in having hippocampal neural correlates. They suggest instead that participants fail to identify some aspects of recollection, misreporting it as familiarity, a problem with word‐like items that have strong and recallable semantic associates.